The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/fare.12021
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction among Dual‐Earner Couples: Gender Ideologies and Family‐to‐Work Conflict

Abstract: This study examines whether the gender ideologies of both spouses moderate how family‐to‐work conflict relates to marital satisfaction among dual‐earner couples. The authors address the research questions using data from a random sample of dual‐earner couples from the northern part of a western state (N = 156 couples). Findings indicate that husbands' gender ideologies moderate how husbands' and wives' family‐to‐work conflict relate to husbands' marital satisfaction. Additionally, husbands' gender ideologies m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
(56 reference statements)
0
12
0
1
Order By: Relevance
“…evolves due to the family duties that obstruct the job duties while the other depicts the inhibition created between the work responsibilities and the family duties (Beutell, 2010;Kinnunen et al, 2010). The previous studies by Minnotte et al (2013); Minnotte et al (2015) show that the relationship between work and family is reciprocal due to W-FC, hence, the negative effect of work on family and the family in turn, affecting work negatively. Briefly, the outcome of previous studies have ascertained that W-FC is associated with increased sales targets, parental discomfort, slowing down of family contentment, job fulfilment and corporate assurance (Karatepe and Kilic, 2007;Lu et al, 2010).…”
mentioning
confidence: 95%
“…evolves due to the family duties that obstruct the job duties while the other depicts the inhibition created between the work responsibilities and the family duties (Beutell, 2010;Kinnunen et al, 2010). The previous studies by Minnotte et al (2013); Minnotte et al (2015) show that the relationship between work and family is reciprocal due to W-FC, hence, the negative effect of work on family and the family in turn, affecting work negatively. Briefly, the outcome of previous studies have ascertained that W-FC is associated with increased sales targets, parental discomfort, slowing down of family contentment, job fulfilment and corporate assurance (Karatepe and Kilic, 2007;Lu et al, 2010).…”
mentioning
confidence: 95%
“…Studies have established that the workfamily conflict exists. [38][39][40] Total rewards programs are associated with employee retention. 41 The results of a recent study of 406 dualincome couples in India showed that dualincome couples had favorable perceptions of the following workplace initiatives: workfamily balance programs, supervisor support, coworker support, workplace autonomy and role clarity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, poor marriage relations seem to be associated with the development of physical and mental maladies (Gottman & Silver, 2000), to the disadvantage of relations with relatives (Benetti, 2006;Bolsoni-Silva & Marturano, 2010), family members in general and friends (Norgren, Souza, Kaslow, Hammerschmidt, & Sharlin, 2004). Personality traits (Solomon & Jackson, 2014), gender (Jackson, Miller, Oka, & Henry, 2014), the existence of offspring (Hernandez & Hutz, 2009), education (Mihalcea, Iliescu, & Dincă, 2013), social and fi nancial status (Ahmadi & Sadeghi, 2016), working for a living (Minnotte, Minnotte, & Pedersen, 2013), prior amorous experiences (Mirecki, Chou, Elliott, & Schneider, 2013), and the dynamics and changes brought by time (Norgren et al, 2004) can all affect the situation, Review of the Marital Satisfaction Scale's Factor Structure. 1993 increasing or decreasing a couple's marital satisfaction, depending upon each particular case.…”
Section: Palabras Clavementioning
confidence: 99%